The role of quality of work life in increasing employee job satisfaction: A study on retail company - Hidayaturrohmah, Elfa; Harahap, Dewi Handayani; Rohyati, Eni; Fatuhrahmah, Ufi (JURNAL SPIRITS, 2025)
As human resources, employees play an essential role in maintaining customer satisfaction, quality, and professionalism. One factor that plays a role in increasing job satisfaction is the quality of work life. Employees with low quality of work life tend to experience decreased job satisfaction, which ultimately impacts work productivity. This study examines the role of quality of work life in improving job satisfaction among employees in retail companies. The study used a quantitative approach with a purposive sampling technique and involved 82 respondents. The instruments used comprised a quality of work-life scale (26 items) and a job satisfaction scale (30 items). The results showed a positive relationship between quality of work life and job satisfaction, with a significance value of 0.383 and an effectiveness contribution of 27.9% (r² = 0.279). This finding shows that the better the quality of work life perceived by employees, the higher the level of job satisfaction they experience in a retail company environment.